The Involvement of Genes in Adolescent Depression: A Systematic Review - Xia, Liangwei; Yao, Shuqiao (Frontiers in Behavioral Neuroscience, 2015)
Numerous studies have reported on the roles of genetic factors in the development of depression in adolescents and young adults. However, there are few systematic reviews that update our understanding of adolescent depression with the biological findings identifying the roles of gene expression and/or polymorphism(s). This review systematically summarized the findings that clearly identified the contribution of a gene to the risk of depression in adolescents between the ages of 10 and 19 years old and young adults between the ages of 20 to 25 years. Data were obtained through searching PubMed, Embase, and Web of Science. A total of 47 studies on early adolescence and 3 studies on young adults were included in the current review. Most articles studied genes in the serotonergic system (n=26), dopaminergic system (n=3), and BDNF gene (n=12). 92.3% of studies (24/26) identified positive associations of 5-HTTLPR polymorphism with depressive illness or depressive symptoms. 83.3% of studies (10/12) found positive association between BDNF Val66Met genotype and adolescent depressive symptoms. More studies should be conducted on the 18 genes reported in a few studies to clarify their roles in the risk for adolescent depression.